The Economic Value Of Toba Batak Marriage Traditions Post Repeal Of PPKM - Purba, Elvis F; Nababan, Tongam Sihol; Lastri, Lastri; Siregar, Tesa EV (LPPM Universitas PGRI Sumatera Barat, 2025)
This research aims to estimate the expenditure on Toba Batak wedding customs from the initial stages to the traditional wedding ceremony by taking an inventory of various expenditures so that the economic value of the wedding custom can be mapped. The economic value referred to is the value paid by consumers (namely paranak and parboru) for goods and services purchased or consumed or used in marriage customs, especially from micro, small and medium enterprises (MSMEs). To collect data, 30 families were selected as research samples with the following criteria: (1) the traditional wedding party was paid for by paranak , (2) the amount of the dowry (sinamot ) was a maximum of 40 million rupiah, (3) the martumpol was held , (4) the traditional party was held in Medan , and (5) paranak and parboru are both Toba Batak people. The sampling method is accidental sampling and data collection starts from March to August 2023. Then the primary data is processed using simple mathematical calculations and analyzed quantitatively descriptively. The research results show a total expenditure of 2,833,900,000 rupiah or an average of 188,926,667 rupiah for each wedding custom. The main source of expenditure is paranak, almost 69% of the total. Meanwhile, the economic value of traditional marriages reached 1,965,600,000 rupiah or an average of 131,040,000 rupiah, namely to pay for goods and service transactions to MSMEs. Paranak contribution to the transaction was around 67% and the rest came from parboru. Assuming 500 marriage customs, the economic value of marriage customs is estimated to reach hundreds of billions in 2023 and become one of the drivers of economic activity, especially for MSMEs in Medan City.